Polyadenylated Telomeric Noncoding RNA Functions as a Pivotal Therapeutic Target of Anti-Ageing to Stabilize Telomere Length of Chromosomes Via Collaborating With Zscan4c - Xu, Xiaojuan; Chen, Zhengju; Wu, Wei; Tian, Xiaohe (Frontiers in Pharmacology, 2022)
Telomeres are closely associated with the development of cell aging. Shortening or erosion of telomeres will cause cell mortality, suggesting that the maintenance of telomere integrity facilitates cell anti-senescence. However, the mechanism of how to keep the telomere length remains fragmentary. Here, we found that polyadenylated telomeric noncoding RNA (TERRA) can promote the self-renewal when overexpressed in mouse embryonic stem cells (mESCs), implying that TERRA with polyadenylation is critical for mESC maintenance. Further studies revealed that TERRA with a polyadenylated tail plays an important role in the sustenance of telomere length. High-throughput sequencing and quantitative real-time PCR show that zinc finger and SCAN domain containing 4C (Zscan4c) may be a potential target of TERRA. Zscan4c is negatively regulated by TERRA and collaborates with TERRA to stabilize the telomere length of chromosomes in mESCs. Our study not only identifies TERRA as a potential novel factor of telomere length regulation and uncovers the new molecular mechanism of cell anti-aging, but also indicates that Zscan4c could be a key therapeutic target candidate for therapy in dysfunctional chromosome diseases. These data will expand our understanding of the cell fate regulatory network and will be beneficial to drug discovery and theragnostics for antiaging and anticancer therapy in the future.